Gender Based Violence in University Communities Policy, Prevention and Educational Initiatives - Anitha, Sundari; Lewis, Ruth (2018)
Until recently, higher education in the UK has largely failed to recognise gender-based violence (GBV) on campus, but following the UK government task force set up in 2015, universities are becoming more aware of the issue. And recent cases in the media about the sexualised abuse of power in institutions such as universities, Parliament and Hollywood highlight the prevalence and damaging impact of GBV. In this book, academics and practitioners provide the first in-depth overview of research and practice in GBV in universities. They set out the international context of ideologies, politics and institutional structures that underlie responses to GBV in elsewhere in Europe, in the US, and in Australia, and consider the implications of implementing related policy and practice. Presenting examples of innovative British approaches to engagement with the issue, the book also considers UK, EU and UN legislation to give an international perspective, making it of direct use to discussions of 'what works' in preventing GBV.